Boss, bxtch, baby. 1 - Dacto (Seven Seas, 2025)
Hojin Koo is in deep trouble. Ruthless loan sharks are after him, demanding payment for a debt his runaway brother left behind. Just when he braces for the worst, a group of suited strangers swoops in to save him. But his relief is short-lived-his rescuer turns out to be a former one-night stand with a wild proposal: become his personal plaything for a year, and the debt disappears. Reluctantly, Hojin agrees. At first, he's nothing more than a pet for the eccentric corporate heir, but as time passes, he glimpses the loneliness beneath the man's wealth and power. As their relationship evolves and emotions stir, is Hojin falling into something real-or just making another terrible mistake?